Upaya Meningkatkan Motivasi Belajar Agama Hindu Melalui Penerapan Model Reading Guide Berbasis PAIKEM di Kelas VI di SD Negeri 3 Cakranegara - Ni Wayan Surasti (LPPM Universitas Pendidikan Mandalika, 2017)
This study aims to examine the effectiveness of the application of PAIKEM Based Reading Model Guide in an effort to increase the students learning activity of Hinduism Class VI of SD Negeri 3 Cakranegara. The benefit of this research is as references in the implementation of the learning process in the real class. For teachers, the result of the study is to improve competence in the learning process and for students it is to improve learning motivation that impacts students learning outcomes. This research was conducted in two cycles; each cycle activity used planning, action, observation and reflection. The final result of action in cycle II showed that the teacher observation result got average score (4,43) and the result of students observation reached average score (4,22). Meanwhile, the result of the increase of students' learning activity wasreflected in the increase of the students learning achievement reaching the average value (77,25). It meant the success indicator of learning (> 75,00) had been exceeded. Thus, because the success indicator has been proven that the research is categorized successful and stopped in cycle II.